SYSTEMATIC IMPORTANCE OF PERIGYNIUM MORPHOLOGY AND ACHENE EPIDERMAL SILICA BODY IN SIXTEEN SPECIES OF CAREX L. (CYPERACEAE) FROM THE DARJEELING AND SIKKIM HIMALAYAS, INDIA.: Life Sciences-Botany - ASOK GHOSH; GAURGOPAL MAITI (International Journal of Life Science and Pharma Research, 2022)
The cosmopolitan genus Carex L. represented about 1,800-2,000 species mainly in temperate and cold regions of the world. 49 species of Carex found in North-eastern India and 33 species in the rest part of India. Systematics of different taxa (subgenera, sections species pairs etc.) of the genus is quite complicated. In Carex, utricle morphology and fruit epidermal silicabodies have been used to delimit species and sections. The present study was undertaken to evaluate the taxonomic utility of these characters within sixteen species of Carex from three subgenera and thirteen sections. The following sixteen species ( viz. Carex baccans Nees, C. myosurus Nees, C. myosurus subsp. spiculata Boott, C. composita Boott, C. cruciata Wahlenberg, C. setigera D. Don, C. breviculmis R. Brown, C. speciosa Kunth., C. insignis Boott, C. polycephala Boott, C. fusiformis Nees subsp. finitima (Boott) Noltie, C. alopecuroides D. Don ex Tilloch and Taylor, C. teres Boott, C. longipes D. Don ex Tilloch and Taylor, C. nubigena D. Don ex Tilloch and Taylor and C. remota L. subsp. rochebrunii (Franchet and Savatier) Kükenthal) are evaluated in the present study. Perigynia of all the studied species are more or less similar in their surface morphology. Surface appears smooth when examined with a dissecting microscope. However, the epidermal cells have a distinctive morphology when viewed under higher magnification; differ significantly in micromorphology (SEM-analysis). Perigynia have epidermal cells with thin convex/concave outer wall that are collapsed in dried specimen. Variation in size, shape, color and number of nerve/costa and texure of utricle are noticeable. Costal cells are narrower and more elongated, but also have thin, collapsed cell wall. Several species have conspicuously nerved, stipitate perigynia others were not. Epidermal cells of achene were polygonal to rhomboidal with little variation in size and shape. Epidermal cells of fifteen out of sixteen species (except Carex nubigena D. Don ex Tilloch and Taylor) each have a single, rounded or nodulose silica body with a basal platform. Although many unique characters were lacking, but interspecific variation in silica bodies was consistent with the high level of morphological variation of utricle and previously detected reproductive variation. The inclusion of micromorphological characters substantially enhances the resolving power of macromorphologic characters in taxon analysis. These data indicated that utricle morphology and micromorphological achene epidermal features (SEM features) are useful in identification of thirteen sections and sixteen species of Carex.